Long-chain acyl-CoA synthetase 1 interacts with key proteins that activate and direct fatty acids into niche hepatic pathways - Young, Pamela A. (J Biol Chem, 2018)
Fatty acid channeling into oxidation or storage modes depends on physiological conditions and hormonal signaling. However, the directionality of this channeling may also depend on the association of each of the five acyl-CoA synthetase isoforms with specific protein partners. Long-chain acyl-CoA synthetases (ACSLs) catalyze the conversion of long-chain fatty acids to fatty acyl-CoAs, which are then either oxidized or used in esterification reactions. In highly oxidative tissues, ACSL1 is located on the outer mitochondrial membrane (OMM) and directs fatty acids into mitochondria for β-oxidation. In the liver, however, about 50% of ACSL1 is located on the endoplasmic reticulum (ER) where its metabolic function is unclear. Because hepatic fatty acid partitioning is likely to require the interaction of ACSL1 with other specific proteins, we used an unbiased protein interaction technique, BioID, to discover ACSL1-binding partners in hepatocytes. We targeted ACSL1 either to the ER or to the OMM of Hepa 1–6 cells as a fusion protein with the Escherichia coli biotin ligase, BirA*. Proteomic analysis identified 98 proteins that specifically interacted with ACSL1 at the ER, 55 at the OMM, and 43 common to both subcellular locations. We found subsets of peroxisomal and lipid droplet proteins, tethering proteins, and vesicle proteins, uncovering a dynamic role for ACSL1 in organelle and lipid droplet interactions. Proteins involved in lipid metabolism were also identified, including acyl-CoA–binding proteins and ceramide synthase isoforms 2 and 5. Our results provide fundamental and detailed insights into protein interaction networks that control fatty acid metabolism.